The Role of Self-Concept and Self-Compassion on the Body Image Adolescent Fans of K-Pop Idols - Anak Agung Istri Miranda Parasari; Luh Made Karisma Sukmayanti Suarya (Philanthropy: Journal of Psychology)
Adolescent of K-Pop fans tend to set the appearance of K-Pop idols as the ideal body standard, thus potentially causing body dissatisfaction and forming a negative body image. The aim of this research is to be able to find out the role of self-concept and self-compassion with the body image adolescent fans of Korean Pop (K-Pop) idols through a quantitative approach with multiple linear regression analysis. The research respondents were 131 adolescent K-Pop fans aged 15-22 years in the city of Denpasar. The research results show that self-concept and self-compassion together contribute to five dimensions of body image (appearance evaluation (R2=49,1%), appearance orientation (R2=18,7%), body area satisfaction (R2=32,1%), overweight occupation (R2=8,9%), and self-classified weight (R2=40,5%)). Self-concept partially contributes in appearance evaluation, appearance orientation, body area satisfaction, and self-classified weight, while self-compassion contributes to overweight occupation (p